A cat's day - Rissman, Rebecca; Moor, Becka (Chicago, Illinois Capstone Global Library, LLC, 2015)
"In the first half of this playful flip book, readers follow Lucy the Cat on her wild day through town. To read about Lucy's owner's perspective of the same day, flip the book over and start reading from the back!"--
"Flip me over to read the other side of the story"--Cover
English stories
Two stories bound back to back and inverted
1 2 13
NEW_ZTN_GN
Keywords: Upside-down books -- Specimens; Cats -- Fiction; Upside-down books